2004
DOI: 10.1007/s00253-004-1755-7
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology of desulfurization of diesel: prospects and challenges

Abstract: To meet stringent emission standards stipulated by regulatory agencies, the oil industry is required to make a huge investment to bring down the sulfur content in diesel to the desired level, using conventional hydrodesulfurization (HDS) technology, by which sulfur is catalytically converted to hydrogen sulfide in the presence of hydrogen. These reactions proceed rapidly only at high temperature and pressure and therefore the capital cost as well as the operating cost associated with HDS very high. Biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
133
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(135 citation statements)
references
References 62 publications
0
133
0
Order By: Relevance
“…The reactivity of organosulfur compounds varies widely depending on their structure and the local sulfur atom environment. The conditions depend upon the level of desulfurization required (Gupta et al, 2005).…”
Section: Hydrodesulfurization (Hds)mentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of organosulfur compounds varies widely depending on their structure and the local sulfur atom environment. The conditions depend upon the level of desulfurization required (Gupta et al, 2005).…”
Section: Hydrodesulfurization (Hds)mentioning
confidence: 99%
“…The reactivity of organosulfur compounds varies widely depending on their structure and the local sulfur atom environment. The conditions depend upon the level of desulfurization required (Gupta et al, 2005).HDS of diesel feedstock for a low-sulfur product requires a larger reactor volume, longer processing times, and substantial hydrogen and energy inputs. Deep HDS technology results in various problems in the process, which limit its usefulness: (i) the application of extreme conditions to desulfurize refractory compounds results in the deposition of carbonaceous coke on the catalysts; (ii) exposure of crude oil fractions to severe conditions including temperatures above about 360 u C decreases the fuel value of treated product; (iii) deep HDS processes need large new capital investments and/or have higher operating costs; (iv) the H 2 S that is generated poisons the catalysts and shortens their useful life; (v) deep HDS is affected by components in the reaction mixture such as organic heterocompounds and polyaromatic hydrocarbons (Egorova, 2003;Folsom et al, 1999;Konishi et al, 2000;Monticello, 1996).…”
mentioning
confidence: 99%
“…Additionally, BDS can effectively remove some key sulfur-containing compounds that are among the most difficult for HDS to treat. BDS can be used instead of, or complementary with, HDS [40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Biodesulfurization (Bds)mentioning
confidence: 99%
“…The reduction of sulfur in the spent engine oil is necessary to obtain ultra low sulfur diesel through pyrolysis. Biodesulfurization of spent oil using suitable microorganisms may serve as a promising process to eliminate the organosulfur compounds, as already studied in case of hydrodesulfurized diesel obtained from petroleum crude (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In case of diesel, dibenzothiophene (DBT) and its alkylated homologues are biodesulfurized by the action of microorganisms like Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…These biosurfactants are value-added products which can be used for different industrial purposes, mainly as drilling mud in advanced oil recovery from wells (25). Although a few research studies on the biodesulfurization of diesel have already been reported (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Only a few (26) have been reported on the biodesulfurization of spent engine oil are available in the literature.…”
Section: Introductionmentioning
confidence: 99%